(untitled) (International Journal of Engineering and Computer Science, 2016)
Cloud computing is a computing paradigm for managing and delivering services over the internet. The fundamental guidelines of cloud computing model are computing, storage & programming as an administrator. But the size of computation & demand for higher computation is growing very rapidly which is causing an uneven and heavy workload on cloud resources. One of the core problems which cloud resources scheduling need to solve is the load balance. In the cloud resources scheduling process, if load changes suddenly, this may cause resources scheduling tilt. In this paper, we are presenting a review on the existing soft computing based techniques for the load balancing in cloud computing environment. Also a comparison is made for these existing techniques.